Goose feed using ryegrass as main fiber source - ZHANG SHIZHONG (2017)
The invention relates to a goose feed using ryegrass as a main fiber source. The goose feed comprises the following materials in parts by weight: 55-60 parts of ryegrass, 10-15 parts of corn straw, 1-2 parts of fish meal, 10-15 parts of soybean meal, 2-3 parts of soybean oil, 0.5-1 part of stone powder, 15-20 parts of corn flour, 0.3-0.4 part of table salt and 0.5-0.6 part of dicalcium phosphate. Geese raised by the feed by using the ryegrass as a main fiber source are quick in weight increment, high in food consumption and good in production properties, the growing geese have good digestion capability on energy, crude protein, crude fat, Ca and P in ryegrass, the ryegrass contains enzymes, hormones, organic acid and the like, nutrient substances are easier to digest and absorb, and the digestion and absorption level of the feed is increased. 种以黑麦草做主要纤维来源的鹅饲料，包括以下重量份材料：黑麦草55-60份；玉米秸秆10-15份；鱼粉1-2份；大豆粕10-15份；大豆油2-3份；石粉0.5-1份；玉米面15-20份；食盐0.3-0.4份；磷酸氢钙0.5-0.6份。本发明采用黑麦草做主要纤维来源饲养的鹅增重快、采食量高，具有较好的生产性能，同时生长鹅对黑麦草中能量、粗蛋